Regional Cooperation in The Utilization of Trans-ASEAN Gas Pipelines: An International Law Perspective - Huala Adolf; Setiawan Setiawan; Mutiara Khadijah (Faculty of Law, Universitas Muslim Indonesia, Indonesia, 2022)
The Trans-ASEAN Gas Pipelines was a project of interconnected cross-border pipelines connecting ASEAN countries in a bilateral manner based on the cooperation stipulated in the Memorandum of Understanding of Trans-ASEAN Gas Pipelines. This paper will identify Trans-ASEAN Gas Pipelines with the two (two) cooperation models already practised worldwide, namely the interconnected model and the unified project model. The method used in this article was normative juridical, including the comparative approach and statute approach, by obtaining data from secondary sources. More specifically, this article would elaborate on which cooperation model could be adopted by Trans-ASEAN Gas Pipelines that would effectively govern the project. The results showed that the cooperation of Trans-ASEAN Gas Pipelines was unlike that practised by countries generally since the project consisted of both cross-border pipelines and regasification terminals. The decision to incorporate regasification terminals into the project was made to provide an alternative to the region's depleting gas supply. The model was not known in the cross-border pipeline regime and therefore could not be identified with the already known two models. Although Trans-ASEAN Gas Pipelines were a series of interconnected pipelines in nature, the implementation was not in accordance with the theory. A cross-border pipeline and terminal regasification should not be put together in the same energy transport project as they both have different characteristics, thus making the governance of the project complicated while a harmonized legal framework plays an essential aspect in cross-border infrastructure. Trans-ASEAN Gas Pipelines will only focus on cross-border pipelines and will follow the model of a cooperative project.